The Impact of Human Resource Management on Employee Engagement in Workplace of Primostar, Shanghai - Jing, Zhao; Nuruly, Santi (PT FORMOSA CENDEKIA GLOBAL, 2025)
The dynamic economic landscape of Shanghai necessitates effective human resource management (HRM) strategies to engage employees, whose commitment is crucial for enhancing organizational productivity and competitiveness. Primostar, a leading company in Shanghai, faces significant challenges in maintaining employee engagement amid cultural shifts and a highly competitive market. This study aims to evaluate the impact of HRM practices, including recruitment and selection, training and development, performance appraisal, and compensation, on employee engagement at Primostar. Employing a quantitative research methodology, the study uses a cross-sectional survey design with structural equation modeling to analyze responses from 217 employees. The results reveal that all selected HRM practices significantly influence employee engagement, with performance appraisal showing the most substantial impact. This research contributes to the understanding of HRM's role in fostering employee engagement and provides actionable strategies for HR professionals to enhance workforce motivation and retention in challenging business environments.